El Niño Southern Oscillation influences the abundance and movements of a marine top predator in coastal waters. (8th October 2017) - Sprogis, Kate R.; Christiansen, Fredrik; Wandres, Moritz; Bejder, Lars
Abstract: Large‐scale climate modes such as El Niño Southern Oscillation (ENSO) influence population dynamics in many species, including marine top predators. However, few quantitative studies have investigated the influence of large‐scale variability on resident marine top predator populations. We examined the effect of climate variability on the abundance and temporary emigration of a resident bottlenose dolphin ( Tursiops aduncus ) population off Bunbury, Western Australia (WA). This population has been studied intensively over six consecutive years (2007–2013), yielding a robust dataset that captures seasonal variations in both abundance and movement patterns. In WA, ENSO affects the strength of the Leeuwin Current (LC), the dominant oceanographic feature in the region. The strength and variability of the LC affects marine ecosystems and distribution of top predator prey. We investigated the relationship between dolphin abundance and ENSO, Southern Annular Mode, austral season, rainfall, sea surface salinity and sea surface temperature (SST). Linear models indicated that dolphin abundance was significantly affected by ENSO, and that the magnitude of the effect was dependent upon season. Dolphin abundance was lowest during winter 2009, when dolphins had high temporary emigration rates out of the study area. This coincided with the single El Niño event that occurred throughout the study period. Coupled with this event, there was a negative anomaly in SST and an above average rainfall. These conditions may have affected the distribution of dolphin prey, resulting in the temporary emigration of dolphins out of the study area in search of adequate prey. This study demonstrated the local effects of large‐scale climatic variations on the short‐term response of a resident, coastal delphinid species. With a projected global increase in frequency and intensity of extreme climatic events, resident marine top predators may not only have to contend with increasing coastal anthropogenic activities, but also have to adapt to large‐scale climatic changes. Abstract : We examined the effect of El Niño Southern Oscillation (ENSO) on the abundance and temporary emigration of a resident bottlenose dolphin (Tursiops aduncus) population off south‐west Australia. Models indicated that abundance was significantly affected by ENSO, and that the magnitude was dependent upon season. Abundance was lowest during winter 2009, when dolphins had high temporary emigration rates out of the study area. During this time, there was an El Niño event, negative anomaly in SST and an above average rainfall. These conditions may have affected the distribution of dolphin prey, resulting in the movement of dolphins out of the area.